"You Can Only Give Warmth to Your Baby When It's Too Late": Parents' Bonding With Their Extremely Preterm and Dying Child. (December 2017) - Abraham, Andrea; Hendriks, Manya J.
This study on end-of-life decisions in extremely preterm babies shows that the parents under study experience a multitude of stressors due to the immediate separation after birth, the alienating setting of the neonatal intensive care unit (NICU), the physical distance to the child, medical uncertainties, and upcoming decisions. Even though they are considered to be parents (assigned parenthood), they cannot act as primary caregivers. Instead, they depend on professional instructions for access and care. Embodied parenthood can be experienced only at the end-of-life, that is, during the dying trajectory and after the child's death. Professionally supporting parents during this compressed process (from assigned and distant to embodied parenthood) contributes fundamentally to their perception of being a family and supports their mourning. This calls for the further establishment of palliative and bereavement care concepts in neonatology.